Alternative successful functional recovery of total full-thickness velar defect following recurrent oropharyngeal carcinoma resection: A case report. Issue 6 (November 2020) - Tezuka, Masahiro; Hirahara, Narihiro; Kamikuri, Yuhei; Ishida, Takayuki; Nakamura, Norifumi
Abstract: Oropharyngeal reconstruction represents one of the greatest challenges in the surgical rehabilitation of patients with head and neck cancer. Here, we report a case involving the successful recovery of swallowing and speech functions following the repair of a total full-thickness velar defect due to recurrent oropharyngeal carcinoma resection. Repair involved soft palate reconstruction by rotating a wide palatal tissue flap and using a palatal lift prosthesis with a speech bulb (bulb-PLP). A 42-year-old woman who had undergone mucoepidermoid carcinoma resection in the soft palate and reconstruction using a radial forearm flap was referred to our department by an otolaryngologist for consultation regarding the method of functional recovery after recurrent carcinoma resection. After an otolaryngologist resected the tumor, we performed soft palate reconstruction by rotating the remaining palatal mucoperiosteal tissue flap to minimize the velar defect, aiming for a more physiological condition resulting in complete velopharyngeal closure function. One month after the operation, bulb-PLP was applied to recover the swallowing and speech functions. Postoperatively, speech intelligibility and swallowing function were satisfactorily improved, and the nasalance scores improved to almost the same level as in healthy Japanese subjects. Eight years after the operation, tumor recurrence was not observed. The patient maintained a sufficiently high quality of life.